Hybrid 2D phase unwrapping methodology using spatial fuzzy clustering and neurofuzzy classification with application in sar images - Then, Patrick Hang Hui. (Faculty of Computer Science and Information Technology, 2001)
Existing phase unwrapping (PU) methodology has arbitrary settings in selection of most optimal algorithm for a particular phase image. These arbitraries impose partially trial and error basis in finding for the best phase unwrapping algorithm and tinkering quality map in order to produce the most optimal unwrapped solution. Hence, a hybrid PU methodology is proposed and developed.